CURRENT TRENDS IN DIRECT PULP CAPPING MATERIALS IN PROSTHETIC PURPOSE IN REHABILITATION TREATMENT- A REVIEW - Deçolli Yllka; Mihalaş Elena; Checheriţă Laura Elisabeta; Aminov Liana; Antohi Cristina (Romanian Dental Association for Education, 2020)
Materials and techniques used for direct pulp capping are closely related to the pulp vitality prognosis and long-term success of therapy. In the recent years, the performance and potential of these materials has improved significantly, alongside their capacity to induce formation of a new dentin barrier after pulp exposure. As there is not one single way of performing direct pulp capping, this study aims to report current trends applied to this procedure, and generally accepted characteristics of the most widespread materials - adhesive systems, calcium hydroxide, MTA, and other bioactive endodontic cements.